Synergistic Effects of 2600 MHz Radiofrequency Exposure and Indomethacin on Oxidative Stress and Gastric Mucosal Injury in Rats - Oruc, Sinem; Aral, Bahriye Sirav; Eraslan, Ersen; Erden, Yavuz; Ozkut, Mahmud Mustafa; Gocmen, Ayse Yesim; Ozen, Sukru (Springernature, 2026)
Background/Aim With the widespread use of mobile technologies and NSAIDs, concerns have emerged regarding their potential combined impact on gastric health. This study investigated the synergistic effects of 2600 MHz RFF exposure and IND, a commonly used NSAID, on oxidative stress and gastric injury in rats. Materials and Methods Forty male Wistar albino rats were randomly assigned to five groups: control, sham, IND, RFF, and IND + RFF. Animals were exposed to 2600 MHz RFF (1 h/day, 5 days/week) for 15 days, and/or received IND (4 mg/kg) via intragastric gavage. Gastric tissues were evaluated biochemically for oxidative stress markers (TOS, OSI, MDA, GSSG), antioxidant parameters (TAC, SOD, CAT, GSH, GPx), histologically for tissue damage, and immunohistochemically for HSP70 expression and apoptosis. Results Single exposure to IND or RFF significantly elevated oxidative stress markers and decreased antioxidant levels in gastric tissues (p < 0.001). Combined IND + RFF exposure resulted in markedly greater gastric injury, with pronounced increases in HSP70 expression and apoptotic cell counts compared to single exposures (p < 0.001). Conclusion Co-exposure to 2600 MHz RFF and IND markedly intensified oxidative stress, apoptosis, and gastric mucosal injury in rats. These findings suggest that the combined exposure produces a synergistic detrimental effect, exacerbating gastric tissue damage beyond the impact of each factor alone.
Keywords: Radiofrequency fields; Mobile phone; & Idot;ndomethacin; Oxidative stress; Gastric injury